Pattern recall skills of talented soccer players: Two new methods applied - van Maarseveen, M. J. J.; Oudejans, R. R. D.; Savelsbergh, G. J. P. (Human Movement Science, 2015)
In this study we analyzed the pattern recall skills of talented soccer players by means of two innovative methods of analysis and gaze behavior data. Twenty-two young female soccer players watched video clips of 3 vs. 3 small-sided games and, after occlusion, had to reproduce the positions of the players. Recall performance was measured by calculating the spatial error of the recalled player positions at the moment of occlusion and at consecutive 33 ms increments. We analyzed player positions relative to each other, by assessing geometric pattern features in terms of angles between players, and we transformed the data into real-world coordinates to exclude the effects of the 2D perspective in the video clips. The results showed that the participants anticipated the movements of the patterns. In real-world coordinates, the more experienced players anticipated the pattern further in advance than the less experienced players and demonstrated a higher search rate, a shorter fixation duration and a higher fixation order. The differences in recall accuracy between the defensive and offensive elements were not consistent across the methods of analysis and, therefore, we propose that perspective effects of the video clip should be taken into account in further research. Article outline Highlights Abstract PsycINFO classification Keywords 1. Introduction 2. Method 2.1. Participants 2.2. Stimulus materials 2.3. Procedure 2.4. Data analysis 2.4.1. Traditional recall accuracy 2.4.2. Anticipatory recall accuracy 2.4.3. Accuracy of pattern features 2.4.4. Recall accuracy in real-world coordinates 2.4.5. Gaze behavior 2.4.6. Statistical analysis 3. Results 3.1. Former method of analysis 3.1.1. Advance time 3.2. Geometric pattern features 3.2.1. Advance time 3.3. Real-world coordinates 3.3.1. Advance time 3.4. Gaze behavior 3.4.1. Experience groups 3.4.2. Good vs. bad trials 4. Discussion References